Incidents of Gray Market Activity Among U.S. Exporters: Occurrences, Characteristics, and Consequences - Myers, Matthew B. (Journal of International Business Studies, 1999)
Each year, the value of gray market products sold throughout the world runs into the billions of dollars. Past research has stated that exporters of manufactured goods can hardly afford to ignore the possibility of this phenomenon due to the often severe effects on their sales volume, margins, and relationships with distributors and end-users. Through a survey of export managers of manufacturing firms, coupled with a series of qualitative interviews, this study investigates how organizational specific, control specific, and market specific factors drive gray market activity, and in turn explores the effects of unauthorized distribution on export performance. Several factors are shown to evaluate the potential of unauthorized distribution in their export markets, namely the centralization of decision making, the degree to which the product is standardized, channel integration, and channel control. International experience, market volatility, and the number of markets served were found to have no effect on gray market activity, this contrary to traditional thinking. Furthermore, the effects of gray market activity on strategic versus economic performance is shown to be significantly different. Each of these issues is discussed in detail, along with the implications for export managers.